Treating acne vulgaris: systemic, local and combination therapy. Issue 4 (July 2010) - Savage, Laura J; Layton, Alison M
Optimizing the management of acne vulgaris corresponds with improved outcomes, reduced scarring and a positive influence on the profound psychosocial disability that frequently accompanies this debilitating skin condition. Many effective, cost-effective therapies are widely available, but significant improvement or clearance can only be achieved if these agents are employed with a logical approach. Patient variability makes the definition of optimum treatment strategies difficult, but with due consideration of the pathological mechanisms driving acne in each individual patient, an appropriate combination of topical, systemic and localized therapies can be prescribed that will yield a favorable outcome. In recent years, a range of physical techniques have emerged as an adjunct to conventional treatments, and with increasing patient interest and expectation, extensive research is underway into these and novel medical therapies that may further broaden our therapeutic armamentarium. This article provides details of currently available therapies, reviews the published evidence on efficacy and considers how best to optimize outcomes with a focus on acne pathogenesis.